Preventing theft [videorecording] (Foodservice security video series, 1994)
Shows food service employees how to react when faced with three common types of theft: internal, customer, and external. Tells how to alert management when a co-worker is suspected of stealing and what to do when a customer leaves without paying. Explains the importance of adhering to company policies. Shows how to use care when opening and closing